Promoting NGO–academic partnerships for population, health, and environment learning. Issue 2 (17th February 2017) - Sellers, Samuel
ABSTRACT: Population, health, and environment (PHE) projects integrate family planning, community health, conservation, and livelihoods activities into a single effort. Despite growing calls for integrated services, relatively little academic research on PHE has been published, which has hampered the development of the approach. This article argues that additional partnerships between academics and NGOs are necessary to further advance learning around PHE. However, such partnerships need not be approached in the same way. The article discusses barriers that currently impede the development of stronger partnerships and adapts (Roper, L. 2002. "Achieving Successful Academic-Practitioner Research Collaborations." Development in Practice 12 (3–4): 338–345) typology of NGO–academic partnership models to describe how different relationship types are currently leveraged within the PHE community.